RESPONS PERTUMBUHAN BIBIT KAKAO TERHADAP PEMBERIAN KOMPOS SAMPAH KOTA DAN PUPUK P - Marisi Untung Hutahaean; Balonggu Siagian; Lisa Mawarni (Jurnal Agroekoteknologi, 2013)
The response of cocoa seedlings growth for giving municipal waste compost and P fertilizer. Thedesign of the experiment was randomized block design arranged in factorial with two factors. Thefirst factor is municipal waste compost, Subsoil ultisol 5 kg + municipal waste compost 0 kg,Subsoil ultisol 3,75 kg + municipal waste compost 1,25 kg, Subsoil ultisol 2,5 kg + municipal wastecompost 2,5 kg, Subsoil ultisol 1,25 kg + municipal waste compost 3,75 kg. The second factorpresent of Phosphat Fertilizer, 0 g/polibag, 2 g/polibag, 4 g/polibag, 6 g/polibag. The Parameterobserved includes plant hight (cm), number leafs (sheet), diameter of stem (mm), total of broad leaf(cm2), fresh and dry weight of crown (g), fresh and dry weight of root (g).The result of reseach showed that municipal waste compost influential significantly on plantheight, number of leafs, diameter of stem, total of broad leaf, fresh and dry weight of crown, freshand dry weight of root. P fertilizer was significantly on total of broad leaf. Interaction between ofmunicipal waste compost and P fertilizer was not significantly to all parameters.Key words : cacao, compost, phosphat